Contribution to validation of the Italian version of work ability personal radar - Sottimano, Ilaria; Garzaro, Giacomo; Guidetti, Gloria; Pira, Enrico; Viotti, Sara (La Medicina del Lavoro, 2022)
Background: Work ability (WA) is an important construct in the occupational health field. Over the years, various WA detection tools have been developed, and a new one is: Work Ability Personal Radar (WA-PR), capable of investigating all the dimensions that define the complexity of WA. The WA-PR was born in the Finnish context, however recently it has also been validated elsewhere. In light of literature on WA assessment tools, our goal is to contribute to the validation of the WA-PR in the Italian context. Methods: Data were collected using a self-reported questionnaire administered to 405 workers in the chemical industrial sector. Results: Results show that the WA-PR correlate with WAI and with other constructs conceptually related to work ability: need for recovery, stress and general health. Conclusions: Data analysis confirms that the WA-PR is a useful and reliable tool for evaluating work ability in Italian context.